2015
DOI: 10.1016/j.ccell.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Inhibition of ERK Dimerization Prevents Tumorigenesis by RAS-ERK Pathway Oncogenes

Abstract: Nearly 50% of human malignancies exhibit unregulated RAS-ERK signaling; inhibiting it is a valid strategy for antineoplastic intervention. Upon activation, ERK dimerize, which is essential for ERK extranuclear, but not for nuclear, signaling. Here, we describe a small molecule inhibitor for ERK dimerization that, without affecting ERK phosphorylation, forestalls tumorigenesis driven by RAS-ERK pathway oncogenes. This compound is unaffected by resistance mechanisms that hamper classical RAS-ERK pathway inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
101
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(107 citation statements)
references
References 35 publications
3
101
3
Order By: Relevance
“…Other groups have attempted to tackle mechanisms of resistance related to the appearance of mutations in MEK1/2 and novel MEK inhibitors active in some of these mutants show interesting potential (120). An avenue of action expected to draw increasing attention is the use of ERK inhibitors (121)(122)(123). Whether in combination with BRAF or MEK inhibitors, small molecule inhibitors such as SCH772984 and GDC-0994 are being tested at present.…”
Section: Potential For Alternative Combination Therapiesmentioning
confidence: 99%
“…Other groups have attempted to tackle mechanisms of resistance related to the appearance of mutations in MEK1/2 and novel MEK inhibitors active in some of these mutants show interesting potential (120). An avenue of action expected to draw increasing attention is the use of ERK inhibitors (121)(122)(123). Whether in combination with BRAF or MEK inhibitors, small molecule inhibitors such as SCH772984 and GDC-0994 are being tested at present.…”
Section: Potential For Alternative Combination Therapiesmentioning
confidence: 99%
“…Recent efforts have demonstrated that pharmacologically targeting ERK dimerization can lead to a significant reduction in RAS-driven tumor growth by potently inhibiting phosphorylation of ERK cytoplasmic substrates. The ERK dimerization inhibitor DEL-22379 reduced tumor growth in mutant KRAS xenograft models and was able to overcome upstream resistance mechanisms, including NRAS overexpression and MEK mutation [87] . Among ERK1/2 cytoplasmic substrates that drive tumorigenesis are the RSK serine/threonine kinases.…”
Section: Erk Substratesmentioning
confidence: 99%
“…ERK is also targeted by matrine (21). The ERK pathway plays an important role in cell proliferation, migration and apoptosis (17). Previous studies reported the relationship between matrine and the ERK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The ERK signaling pathway plays an important role in cell growth, survival and apoptosis (17). Studies showed that the inhibition of the ERK pathway positively reduced RMS cell growth, survival, and epithelial-mesenchymal transition (EMT) (7)(8)(9).…”
Section: Matrine Inhibited the Proliferation And Induced Apoptosis Ofmentioning
confidence: 99%